METHODOLOGY OF DISCUSSION OF FUNDAMENTAL FEATURES OF ELEMENTARY PARTICS IN PEDAGOGICAL EDUCATIONAL INSTITUTIONS - Qurbonaliyev Qobiljon Qosimjon o’g’li; Xusanov Omonjon, Abdurafiqov Hayotjon (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the ways in which the formulation of ideas about the fundamental properties of elementary particles is considered in higher education lectures.